2014
DOI: 10.14740/wjnu169w
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac Prescribing Practices in an Acute Care Hospital and the Incidence of Acute Renal Failure

Abstract: Background: Ketorolac has been documented to cause acute kidney injury (AKI) but current data suggest that it is safe for those who have low risk for renal dysfunction. In our facility, there have been cases of AKI in those treated with Ketorolac but the incidence is not known. This study describes the prescribing habits of Ketorolac in our facility and determines the incidence of AKI while on this therapy. Methods:Electronic medical records of patients who received Ketorolac were reviewed during the last 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014). This edema was clearly localized as severe vacuolation in the kidney tubules of co-administrated group, KT/WR, of the present work.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014). This edema was clearly localized as severe vacuolation in the kidney tubules of co-administrated group, KT/WR, of the present work.…”
Section: Discussionsupporting
confidence: 52%
“…The major mechanisms for WR-induced renal toxicity were previously reported as glomerular hemorrhage and tubular dysfunction by obstruction due to RBC casts (Mendonca, Gupta, Valsan, & Tewari, 2017;Ozcan et al, 2012). Similar to Chana et al (2014) who revealed that KT induced acute kidney injury, another NSAID, diclofenac sodium, was found to induce the congestion in the blood vessels, the degeneration in nephrons, and the increase in the connective tissue in rat kidneys (Khoshvakhti et al, 2015). Thus, the combined treatment of KT and WR may be responsible for the accelerated progressive events of acute kidney injury obtained in the current study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“….033 Congestive heart failure 2 ( Direct correlation of ketorolac use and acute kidney injury has been described with mixed results in the literature. A recent retrospective review by Chan et al found that kidney injury with ketorolac was more common in patients 65 and older, had hypertension and/or diabetes [16]. Ying and colleagues found that preoperative NSAID administration in patients undergoing major orthopedic surgery was associated with AKI, as well as a linear relationship between dose and occurrence [17].…”
Section: Discussionmentioning
confidence: 99%
“…Menurut (I., 2011), setelah usia 40 tahun, Glomerular Filtration Rate (GFR) menurun sekitar 10 ml/menit sehingga pada usia 70 tahun GFR telah menurun sekitar 30 ml/menit. Penurunan fungsi ginjal pada penuaan ini bersifat irreversible (Chan et al, 2014). Proses penuaan juga diperparah oleh faktor klinis yang menjadi faktor resiko terjadinya penyakit gangguan ginjal.…”
Section: Karakteristik Responden DI 8 Domain Qol Sf-36unclassified